Synthesis of silicon-based polymers for solid state lithium polymer batteries - Vangol, Pratap; Baksy, Aronya (International Journal of Engineering and Technology, 2018)
This paper proposes the utilization of silicon based polymers for solid state lithium polymer batteries, thereby allowing batteries to be more rugged by decreasing electrolyte volatility and also making them eco-friendly.Â Â Â